AI-Based Teaching Materials for Deep Learning: An Analysis of Usage by Elementary School Teachers - Sunaengsih, Cucun; Komariah, Aan; Kurniady, Dedy Achmad; Salsabil, Syifa Hanifa (International Journal of Educational Management and Innovation, 2025)
Background/purpose. This study investigates the development of AI-powered learning materials to enhance elementary school teachers' professional learning. This is in consideration of the low utilization of AI technology in developing learning materials in the teaching process. The primary objective of this study is to investigate the extent of utilization of AI-based learning materials among elementary school teachers. Materials/methods. This study utilized a quantitative descriptive study using a survey method with 231 elementary school teachers in West Java, Indonesia, as participants. Results. The findings show that most teachers have begun incorporating AI-based teaching materials and find them helpful in enhancing student comprehension and participation, despite ongoing issues of training and infrastructure. Conclusion. The study concludes that AI-powered instructional materials can leverage deep learning to the maximum in primary education, subject to sufficient training and infrastructure. The findings are likely to inform future research in formulating the professional development requirements of teachers for planning AI-enabled instructional materials for effective facilitation of deep learning.